Analisis Penerimaan Pengguna terhadap Financial Technology Bareksa Menggunakan Model UTAUT - Syahrul Maulana; Iiswatun Khasanah; Abdul Yusuf (Universitas Proklamasi 45, 2023)
Financial Technology (Fintech) is a set of financial services, tools, platforms, and ecosystems that make financial products and services easier and cheaper to access. One example of the application of Fintech in financial transactions is Bareksa. User acceptance of Bareksa may be influenced by various factors, to find out more about that, this research was carried out. The purpose of this study is to find out how the perception of user acceptance and what factors influence users to use Bareksa. This study uses the Unified Theory of Acceptance and Use of Technology (UTAUT) model as the theoretical basis. The population and sample in this study were Bareksa users and the sampling technique used was quota sampling by obtaining 120 pieces of data. The research method uses Structural Equation Modeling (SEM) with the bootstrap technique because the processed data is not normally distributed. The results of this study are user acceptance of Bareksa is influenced by factors of Business Expectations and Behavioral Intentions, while the factors of Performance Expectations, Social Influences, and Facility Conditions do not affect user acceptance to use Bareksa.